PENGARUH BENTUK TURBULATORS TERHADAP EFISIENSI SOLAR AIR HEATER DENGAN PENAMBAHAN SENSIBLE HEAT STORAGE MATERIALS - Faradin Adyatama; Intan Hardiatama; Mahros Darsin (Jurnal Teknologi, 2023)
Indonesia is an equatorial country. This makes Indonesia has a very abundant source of solar energy in Indonesia. One of the tools that can be developed using solar energy is solar air heaters. In its application, solar air heaters have weaknesses, one of which is the low heat transfer coefficient. In this study a reasonable amount of turbulator and heat storage material is used to increase the proportion of heat research. The purpose of this research is to study the variation of turbulator variations and the distance of each turbulator that is 2.5 cm and 3.5 cm to the efficiency of solar air heaters. Tests carried out using three halogen lamps as solar radiation. The radiation beam is controlled with a dimmer and monitored via a digital multimeter. The value of the intensity of radiation used is 577 W/m2; 675.6 W/m2; 730.2 W/m2; and 881.2 W/m2. Blowers are used as forced convection with mass flow rates of 0.0083 kg/s. The results show that the shape of the crimp turbulator can increase efficiency twice as much as the staggered turbulator, which is 25% and 50%, respectively for each crimp turbulator and staggered turbulator. The addition of the turbulator distance in the crimp turbulator can increase efficiency by 5%. However, the magnitude of the turbulator in the staggered turbulator decreases efficiency by 5%. This proves the importance of spacing so that it can achieve optimal results.